If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(3x-4)=x-4
We move all terms to the left:
3(3x-4)-(x-4)=0
We multiply parentheses
9x-(x-4)-12=0
We get rid of parentheses
9x-x+4-12=0
We add all the numbers together, and all the variables
8x-8=0
We move all terms containing x to the left, all other terms to the right
8x=8
x=8/8
x=1
| (9x+23)(10x+6)=180 | | 2(3x-8)=(6x+4)-15×2x | | x/5=2.2 | | (6x+26)=(2x+18) | | 27=(-30-8y) | | 4g−4=−24 | | 3+2q=9 | | (30-2x)(80)=1776 | | 2(3x-8)=6x+4-15×2x | | -2/5=-7/8v+5/4 | | 3(2x-1)-2x=21 | | (30-2x)(80-2x)=1776 | | x+35+90=180 | | -6v+30=4(v-5) | | 6x-12+2x-8=12x+12 | | -3x+79(x+5)=5x+38 | | 3.2x=11.52= | | 4/25=x/100 | | 25x+x=375 | | (2u+1)(9-u)=0 | | x-20=58 | | 20x+100=10x-50 | | 11-2x=6-3x | | 5.1=3x-4.2 | | 1-(156x+624)=6 | | 4x+34=12x+54 | | k+4÷0.2=5 | | 2=3/4x | | -15=5a | | x/6+6=11 | | x=825+3.25x | | 1/8x12=X |